MENGGALI LANGKAH PREVENTIF UNTUK MENCEGAH POSPARTUM DEPRESSION SYNDROME BAGI CALON AYAH DAN IBU PASCA MELAHIRKAN - Citra Widyastuti; H Hasriani (Al-Isyraq: Jurnal Bimbingan, Penyuluhan, dan Konseling Islam, 2023)
Childbirth is an event experienced by all normal women. On that occasion, generally women or parents will feel happy for the presence of the baby. However, in some cases some women experience anxiety and even depression during childbirth. Many factors affect a woman's depression after giving birth, both internally and externally. This symptom is known as postpartum depression or postparum depression syndrome. Therefore, women must prepare everything to deal with the possibilities that occur. In this journal, researchers discuss prevention efforts that can be carried out by both prospective mothers and fathers. This study uses a qualitative approach. Where in the discussion, researchers try to describe several ways of prevention after observing several local and international journals. This type of research is a literature study or literature study. The data were taken from several literature sources and analyzed to be used as the results of the discussion in this study, after which it was concluded. The purpose of this study is to analyze various ways of preventing the occurrence of postpartum depression, thus the results of this study can be a reference for further research and readers who need to be used as guidelines in preventing or overcoming postpartum depression in women or men as parents of new children. born.